PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS WEB MELALUI INTEGRASI PLATFORM SIPEJAR PADA MATA KULIAH CAD DENGAN PENDEKATAN PROJECT BASED LEARNING - Karim, Saifuddin; Pradani, Yayi Febdia; Muhtarom, Imam; Wahyudi, Dian Julianto; Harlin, Harlin (Steam Engineering, 2025)
This study aims to develop a web-based instructional package integrated with the SIPEJAR platform for the Computer Aided Design (CAD) course at Universitas Negeri Malang, employing a Project Based Learning (PjBL) approach grounded in social constructivism. The development process followed the ADDIE model through the stages of analysis, design, development, implementation, and evaluation. Validation by content and media experts indicated high feasibility with scores above 85%. Implementation in a blended learning setting revealed significant improvements in students’ comprehension (from 16.7% to 73.3%), engagement (from 10% to 83.3%), learning satisfaction (from 16.7% to 76.7%), and motivation, which increased among all respondents. Findings highlight that the developed package is not only technically feasible but also enhances collaborative interaction, critical thinking skills, and student readiness for industry demands. This study contributes to contextual digital learning design in technical education and recommends broader application to similar courses along with the integration of learning analytics for continuous improvement.